Full-Wave Analysis of Ultrahigh Electromechanical Coupling Surface Acoustic Wave Propagating Properties in a Relaxor Based Ferroelectric Single Crystal/Cubic Silicon Carbide Layered Structure - Xiaojun Ji; Qiang Xiao; Jing Chen (Modelling and Simulation in Engineering)
This paper describes a full-wave analysis of ultrahigh electromechanical coupling surface acoustic wave (SAW) of Y-cut X propagating Pb(In1/2Nb1/2)O3-Pb(Mg1/3Nb2/3)O3-PbTiO3 (YX-PIMNT) single crystals on a cubic silicon carbide (3C-SiC) substrate. There are several eigenmodes including shear horizontal (SH) and Rayleigh SAWs. Based on the finite-element method (FEM), the phase velocity (vp) and coupling factor (K2) of SAWs varying with the top electrode thickness, thickness, and Euler angle (θ) of the YX-PIMNT substrate have been investigated. K2 of SH SAW can reach an extremely high value of 75.9%. The proper control of structural parameters can suppress unwanted responses caused by other modes without deteriorating the coupling factor. The large K2 value of SH SAW and suppression of unwanted responses have highly promising applications in developing ultrawideband and tunable SAW filters. Finally, the performance of 3C-SiC and 6H-SiC as substrates was investigated, and 3C-SiC was identified as a more attractive substrate candidate than 6H-SiC.